"Do Not Turn a Deaf Ear or a Blind Eye on Me, as I Am Your Son": New Conceptions of Childhood and Parenthood in 18th- and 19th-Century Jewish Letter-Writing Manuals. Issue 1 (2nd January 2016) - Kogman, Tal
ABSTRACT: This article focuses on the cultural functions of Hebrew letter-writing manuals published in German-speaking countries in the 18th and 19th centuries, aimed at young people. I argue that these books, which were used frequently as textbooks for studying Hebrew writing, conveyed modern ideological values and at the same time corresponded to the particular requirements of the traditional Jewish audience. They also bear witness to a marked shift in the conceptions of childhood and of education within the Jewish realm, as their emphasis on sons' duties toward their fathers was gradually replaced by a growing sensitivity toward their young audience's needs.